INTEGRASI VISUAL-ARSITEKTURAL BERBASIS AUGMENTED REALITY PADA PENGEMBANGAN DESA WISATA KABA-KABA, TABANAN (Jurnal Arsitektur ARCADE, 2026)
Augmented Reality (AR) has emerged as an interactive technology capable of enhancing visual information delivery in tourism promotion. This study aims to implement and evaluate the integration of visual-architectural elements based on Augmented Reality as a supporting medium for promoting Kaba-Kaba Tourism Village, Tabanan, Bali. The research employs a research and development approach, encompassing tourism potential data collection, three-dimensional (3D) object modeling, AR integration using marker-based technology, and the development of AR-based promotional brochures. System functionality was tested using blackbox testing to ensure that all main features operated as expected. The results indicate that AR can effectively present visual-architectural representations of tourism objects in an interactive and contextual manner. However, the use of printed brochures as AR markers presents technical limitations related to marker size, scanning distance, and smartphone camera focus. Therefore, AR-based brochures are more suitable as an introductory promotional medium rather than a primary platform for in-depth exploration. This study contributes to the development of applied AR technology for rural tourism promotion while providing practical recommendations for future implementation.
Keywords: Augmented Reality, Tourism Village, Visual Architecture